2014
DOI: 10.1103/physrevb.89.020511
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic changes in the electronic structure upon transition to the collapsed tetragonal phase in CaFe2As2

Abstract: We use angle-resolved photoemission spectroscopy (ARPES) and density functional theory (DFT) calculations to study the electronic structure of CaFe2As2 in previously unexplored collapsed tetragonal (CT) phase. This unusual phase of the iron arsenic high temperature superconductors was hard to measure as it exists only under pressure. By inducing internal strain, via the post growth, thermal treatment of the single crystals, we were able to stabilize the CT phase at ambient-pressure. We find significant differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 57 publications
14
53
0
Order By: Relevance
“…16,23 In addition, in sharp contrast to the paramagnetism in the T phase, intrinsic superconductivity is absent in the cT phase. Recent angle-resolved photoemission spectroscopy (ARPES) measurements show that the two electron pockets at the M point transform into one cylinder, and the hole pockets at Γ disappear, [32][33][34] being in agreement with the band structure calculations. 23,35,36 However, in a de Haasvan Alphen effect study on CaFe 2 P 2 , which is a structural analogue of the cT phase of CaFe 2 As 2 , the hole pockets are not completely vanished, two small hole pockets centered at Z point still exist.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…16,23 In addition, in sharp contrast to the paramagnetism in the T phase, intrinsic superconductivity is absent in the cT phase. Recent angle-resolved photoemission spectroscopy (ARPES) measurements show that the two electron pockets at the M point transform into one cylinder, and the hole pockets at Γ disappear, [32][33][34] being in agreement with the band structure calculations. 23,35,36 However, in a de Haasvan Alphen effect study on CaFe 2 P 2 , which is a structural analogue of the cT phase of CaFe 2 As 2 , the hole pockets are not completely vanished, two small hole pockets centered at Z point still exist.…”
Section: Introductionsupporting
confidence: 65%
“…Very recently, the angle resolved photoemission spectroscopy (ARPES) investigations on the cT phase of CaFe 2 As 2 single crystals suggest that the hole pockets near Γ point sink below the Fermi level while the electron band moves to a higher binding energy, resulting in a decrease of the band effective mass of electron pocket. [32][33][34] Evidently, if we associate the narrow Drude component with the electron pocket and the broad one with the hole pocket, we can attribute the increase of ω 2 p,n to the reduction of band mass of electron pocket and the decrease of ω 2 p,b to the partial removal of hole pocket (mainly close to Γ point). In an earlier study on various 3d transition metal based 122 compounds, Cheng et al found that the moderate 3d-electron correlation is responsible for the incoherent term (the broad Drude term here) in the iron pnictides.…”
Section: Resultsmentioning
confidence: 99%
“…While in the CT phase, those values of α CT and β CT are 5.7 ± 0.1 m e and 2.0 ± 0.1 m e respectively. The reduction of effective mass indicates the suppression of electronic correlations in the CT phase, which is also the case in CaFe 2 As 2 [17,[36][37][38]. For iron-based superconductors, it was proposed in the strong-coupling pairing scenario that the superconducting pairing is mediated by the local antiferromagnetic exchange interaction [39], which is linked to the reasonably strong electronic correlations or narrow bandwidth [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CT phase was found to be stabilized under ambient pressure through introducing chemical pressure by specific dopants or thermal treatment [14,15]. Subsequent ARPES experiments on Ca(Fe 1−x Rh x ) 2 As 2 [16] and the annealed CaFe 2 As 2 [17,18] have revealed significant differences in the electronic structure between the high temperature tetragonal (HT) phase and the CT phase. The predicted vanishment of the hole pocket at the zone center [9,19,20] has been confirmed in both cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation